The burden of thyroid cancer and its association with national development levels in Asia: evidence from 47 countries (1990–2021) - Qin, Wenyi; Lin, Jiong; Zhang, Zhi; Xu, Tuo; Li, Siyi; Chen, Weijie; Liu, Muge; Li, Baibei; Luo, Haiqing; Lili, Yu (Frontiers in Oncology, 2025)
ObjectiveThis study examines the trends in thyroid cancer incidence and mortality and explores their relationship with national development levels.MethodsData on thyroid cancer from 47 countries were sourced from the Global Burden of Disease 2021 study, covering the years 1990–2021. National development was measured using the Human Development Index (HDI), Social Progress Imperative (SPI), Nutrition and Medical Care (NMC), the Density of Doctors per 100,000 population (DOD), and Personal Healthcare Spending (PHS). Correlations between these indicators and thyroid cancer burden were analyzed using scatterplot matrices, heat maps, and principal component analysis (PCA). The mortality-to-incidence ratio (MIR) served as a proxy for thyroid cancer survival rates.ResultsIn 2021, thyroid cancer caused 44,798 deaths globally, up from 21,893 in 1990. Asia accounted for 62.8% of the cases. Among the working-age population, deaths ranged between 10,477 and 27,187, while incidence rates rose from 1.41 per 100,000 in 1990 to 3.36 per 100,000 in 2021. Nine out of the top ten countries in terms of incidence were classified as high or very high in HDI. The incidence of thyroid cancer correlated positively with HDI (Corr = 0.365), SPI (Corr = 0.384), and NMC (Corr = 0.332), particularly among men. Mortality, however, showed a negative correlation with HDI (Corr = -0.401), NMC (Corr = -0.437), and PHS (Corr = -0.446). The global MIR dropped from 0.135 in 1990 to 0.068 in 2021, though Asia saw a 21.1% rise in mortality and a 138% increase in incidence among the working-age population.ConclusionThe rising incidence of thyroid cancer in Asia, particularly in developed nations, has contributed to a global increase, though improved prognoses have led to better survival outcomes over time.